Change in the organization socialization of a basic law enforcement academy: how supervisors cope. (15th January 2021) - Manjarrez, Victor M.
ABSTRACT: This study examines the impact of a changed organizational socialization process on how supervisors cope and adapt in their occupational role. The research study is motivated by the central question: how do supervisors adapt in their occupational role when the initial organizational socialization process has changed. Thirty-two supervisors from the United States Border Patrol served as the research study population. The supervisors were interviewed to understand the organization's socialization process, how they coped with the change, and the impact to their supervisory role. Study participants described how expectations and experiences developed at the basic training academy were foundational for role adaptation and coping with the organizational change. The findings illustrate the persuasiveness of the profession's socialization process is on role adjustment. The findings also highlight the need by organizations to develop supervisory leadership programs that include helping supervisors shape their interpretations and coping strategies during organizational change.